The performance of primary health care in the management of the Covid-19 in Iran and the existing challenges and strategies on the way to confront the pandemics: A qualitative study - Elham Shami; Kamal Gholipour; Simin Khayatzadeh; Saber Azami-Aghdash (Journal of Education and Health Promotion)
BACKGROUND: Primary healthcare (PHC) in Iran, like in other countries, has a fundamental role in managing COVID-19 despite facing various challenges. Therefore, the aim of this study was to qualitatively analyze the performance of PHC in the management of COVID-19 and identify the existing challenges, as well as strategies. MATERIALS AND METHOD: The data for this qualitative study with a conventional content analysis were collected through interviews. The participants of the study were PHC employees, managers, and experts who had high experience and knowledge in the field of the study. The participants of the study were selected using purposeful sampling. The data were analyzed manually using the Granhiem and Landman method. RESULTS: PHC performance was divided into five main themes and 13 subthemes, including epidemic diagnosis, training, making changes to respond, care and vaccination, cooperation, and coordination. Six main themes and 19 subthemes were categorized as the challenges of dealing with COVID-19, which are inputs and structure, infectious disease control and management, management and policymaking, community support, education and evidence management, and providing care services. Strategies were categorized into four main and 16 subthemes. The main strategies were making preparations before the epidemic, reviewing at all levels of PHC, cooperation and coordination, and integrated information. CONCLUSION: The results of this study can be used by authorities and policymakers to prepare well for possible future pandemics.